(untitled) (Bangladesh Journal of Animal Science, 2013)
Innovative methods in relation to rumen microbiology are mainly focused on the study of rumen microbial population. Rumen ecosystem is highly responsive to changes in diet, age, antibiotic use, health of the host animal, which varies according to geographical location, season, and feeding scheme. Until recently, knowledge of rumen fermentation was primarily studied using classical culture-based techniques, such as isolation, enumeration and nutritional characterization, which probably only account for 10 to 20% of the rumen microbial biomass. An increase in bacterial numbers recovered from the rumen is the most reproducible effect of dietary yeast supplementation, and it has been recognized that the increased bacterial population especially cellulolytic bacteria is central to the action of the yeast in improving ruminant productivity . Many DNA based methods have described the diet dependent shift in the diversity of rumen bacterial population. This paper is primarily aimed to see different DNA based methods for study rumen bacterial population. DOI: http://dx.doi.org/10.3329/bjas.v41i2.14134 Bang. J. Anim. Sci. 2012. 41 (2): 141-146